Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have the following equation: $a(x)k-b(x)=0\Rightarrow k=\dfrac{b(x)}{a(x)}$. I find approximate solutions around $x=0$ by two ways:

(1) I expand the equation as $[a(0)+xa'(0)]k-[b(0)+xb'(0)]=0\Rightarrow k=\dfrac{b(0)+xb'(0)}{a(0)+xa'(0)}$.

(2)I expand the solution itself, $k=\dfrac{b(x)}{a(x)}\approx \dfrac{b(0)}{a(0)}+x\left(\dfrac{\partial(b/a)}{\partial x}\right)_{x=0}.$

Why solution (2) is better than solution (1)? And in what cases both the solutions can be almost equal?

share|cite|improve this question
up vote 1 down vote accepted

Both solutions are valid for small $x$, but (2) is better because it is simpler while having the same magnitude of error with respect to the original solution $b(x)/a(x)$. The way we express this is to say that both approximations are valid to $O \left ( x^2 \right )$. Google "big-O notation" for more details.

You can see that both approximations are equivalent to this magnitude of error by Taylor expanding approximation (1) and writing out the derivative term in approximation (2).

Let $a(0) := a$ and $b(0) := b$, etc. Then

$$ \frac{a + a' x}{b + b' x} = \frac{a}{b} \frac{1+ \frac{a'}{a} x}{1+ \frac{b'}{b}x}$$

$$ = \frac{a}{b} \left [ 1 + \left ( \frac{a'}{a} - \frac{b'}{b} \right ) x + O \left ( x^2 \right ) \right ] $$

$$ = \frac{a}{b} + \left ( \frac{a'}{b} - \frac{a b'}{b^2} \right ) x + O \left ( x^2 \right ) $$

Note that the term in the parentheses in the last expression is the derivative of $a(x)/b(x)$ at $x=0$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.